PHF19 promotes the proliferation, migration, and chemosensitivity of glioblastoma to doxorubicin through modulation of the SIAH1/β–catenin axis. Issue 11 (November 2018) - Deng, Qing; Hou, Jianbing; Feng, Liying; Lv, Ailing; Ke, Xiaoxue; Liang, Hanghua; Wang, Feng; Zhang, Kui; Chen, Kuijun; Cui, Hongjuan
Abstract PHD finger protein 19 (PHF19), a critical component of the polycomb repressive complex 2 (PRC2), is crucial for maintaining the repressive transcriptional activity of several developmental regulatory genes and plays essential roles in various biological processes. Abnormal expression of PHF19 causes dysplasia or serious diseases, including chronic myeloid disorders and tumors. However, the biological functions and molecular mechanisms of PHF19 in glioblastoma (GBM) remain unclear. Here, we demonstrated that PHF19 expression was positively associated with GBM progression, including cell proliferation, migration, invasion, chemosensitivity, and tumorigenesis. Using XAV-939, a Wnt/β-catenin inhibitor, we found that the effects of PHF19 on GBM cells were β-catenin-dependent. We also demonstrated that PHF19 expression was positively correlated with cytoplasmic β-catenin expression. PHF19 stabilized β-catenin by inhibiting the transcription of seven in absentia homolog 1 (SIAH1), an E3 ubiquitin ligase of β-catenin, through direct binding to the SIAH1 promoter region. Taken together, our results revealed the novel PHF19-SIAH1–β-catenin axis as a potential and promising therapeutic target.